A suitable development trend in linear city based on smart growth : a case study in Lanzhou urban area - Zhou Wei, 1987-; Soheil Sabri, supervisor; Fakulti Alam Bina (2013)
Thesis (Sarjana Sains (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2013